Impact of organic matter and sand on soil characteristics, leaf area, and chlorophyll of sweet corn (Zea mays saccnutritionta Sturt) on Vertisol from Bojonegoro - Sasongko, Purnomo Edi; Mindari, Wanti; Jayanti, Fara Amilia; Fatiha, Chosa Zahro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Vertisols contain clay minerals that expand significantly during the rainy season and shrink during the dry season. This condition causes changes in the availability of water and soil ions. This study aimed to examine the effect of adding organic matter (OM) and sand on changes in vertisols and plant growth. The study was conducted using a factorial Randomized Block Design (RBD). The first factor was 5 kinds of OM: control (B0), 15 tons of banana peel compost ha⁻¹ + cow dung (10:1) (B1), 15 tons of leaf litter compost ha⁻¹ (B2), 15 tons of water hyacinth compost ha⁻¹ + cow dung (1:1) (B3), and 1 ton of biochar ha⁻¹ (B4). The second factor was the provision of sand as much as 3 level, namely: 0% (P0), 20% (P1), and 40% (P2). Each treatment combination was repeated 3 times. Sweet corn was used as a growth indicator. The observed soil chemical parameters were soil pH, organic C, NH₄⁺ and NO₃⁻, and Cation Exchange Capacity (CEC) using standard methods. Leaf area was measured using the Arnon method. The results showed providing banana peel compost + cow dung with 40% sand increased the best NO₃⁻ and soil pH levels. The highest soil C-organic content was found in the treatment with aloe vera compost + cow dung and 0% sand. The best leaf area and plant chlorophyll levels were achieved using banana peel compost + cow dung with 20% sand.